(untitled) (Bangladesh Medical Journal Khulna, 2019)
Background: In the very recent years, laparoscopic appendicectomy is widely accepted for the surgical procedure of acute appendicitis. Though the application of laparoscopic technique for appendicectomy is expanding very rapidly and now performed in almost all major cities and tertiary level hospitals in our country, but the reports are scanty and conflicting in our surgical practice. Objective: This prospective clinical study was conducted to evaluate the outcome of laparoscopic appendicectomy in acute appendicitis in terms of complication, post surgical pain, conversion rate, negative appendicectomy and duration of hospital stay. Methods: The study was carried out taking a total number of 93 patients of which 53 fulfilled the inclusion criteria admitted in BIRDEM General Hospital, Dhaka and 40 such patients from Khulna Medical College Hospital Khulna and a private clinic in Khulna City during the period from April, 2016 to August, 2018 with the patients of laparoscopic appendicectomy (LA) for acute appendicitis. Data was collected on history and clinical examination, investigation, histopathological examination and post operative complication. Results: Among total 93 patients, majority of the patients were in age group of 20 to 30 years in both sexes and 65.6% were male and 34.4% were female. In case of 06(6.5%) patients negative appendicectomy were done and in 09(9.7%) patients conversion to open appendicectomy was required. Post operative complications like port site bleeding and infection were 4.3% and 2.1% respectively. Majority (87.10%) patients were discharged within 72 hours of LA. Conclusion: This study reveals that laparoscopic appendicectomy is a minimally invasive and relatively safe procedure for acute appendicitis. Bang Med J (Khulna) 2018; 51 : 12-15